Fatigue behaviour evaluation of dissimilar polymer joints: Friction stir welded, single and double-rivets. (August 2018) - Eslami, Shayan; Farahani, Behzad V.; Tavares, Paulo J.; Moreira, P.M.G.P.
Highlights: Fatigue life assessment of dissimilar lap-jointed polymers. Comparison between fatigue life of friction stir welding and riveting methods. Temperature variation measurements in the failure region. Analyzing of the different failure modes subjected to the cyclic loading. Abstract: This article focuses on fatigue life assessment of dissimilar lap-joined polymers. The strength of the friction stir welded polypropylene-to-polyethylene specimens under cyclic loading conditions was analysed. The fatigue life of the strongest welds was compared to both the parent material and blind riveting method with single and double-riveted specimens, in order to compare the welded specimens with available commercial joining techniques. The fatigue lives of the friction stir welded and double-riveted specimens are similar, and they are of the same order of magnitude of the highest performing base material. In order to visualize the temperature variation induced by cyclic loading conditions, a thermographic camera was employed to monitor temperature distribution in the failure region during fatigue testing. For the double-riveted and the parent material specimens, thermal fatigue failure occurred due to temperature increase under cyclic loading. For these two types of specimens, thermal failure occurred when the temperature reached approximately 50 °C in the failure region. Both, the friction stir welded and single-riveted specimens behaved differently from the remaining joints without any significant temperature increase during fatigue testing. The friction stir welded joints presented a brittle failure from the retreating side of the weld nugget, which suffers from defect formation when compared to the advancing side. The single-riveted method produced the weakest joint due to the stress concentration on the drilled hole, while adding a secondary rivet in the same overlapped area created strong joints due to the load transfer among the two rivets.